Afforestation enhanced soil CH4 uptake rate in subtropical China: Evidence from carbon stable isotope experiments. (March 2018) - Wu, Junjun; Li, Qianxi; Chen, Jingwen; Lei, Yao; Zhang, Qian; Yang, Fan; Zhang, Dandan; Zhang, Quanfa; Cheng, Xiaoli
Abstract: Afforestation plays an important role in regulating the methane (CH4 ) exchange between soil and atmosphere. However, it is not fully understood how afforestation affects soil CH4 flux and the carbon isotopic signature of CH4 . We conducted a year-long measurement of CH4 in afforested land (woodland and shrubland) and the adjacent cropland using the static chamber-gas chromatographic technique in the Danjiangkou Reservoir of central China. The soil exclusively functioned as a sink for atmospheric CH4 through the entire study period across land use types. Land use types significantly impacted the CH4 uptake rate with the largest average CH4 uptake rate in the shrubland (37.22 μg m −2 ·h −1 ), followed by the woodland (27.75 μg m −2 ·h −1 ) and the cropland (14.34 μg m −2 ·h −1 ). The mean annual CH4 uptake rates increased in the shrubland by 186.3% and the woodland by 93.5%, compared to the cropland. The isotope fractionation factor (αsoil ) was lower in the woodland and shrubland, compared to the cropland. The CH4 uptake rates and αsoil exhibited similar seasonal patterns among land use types, with a higher CH4 uptake rates and lower αsoil in spring and summer compared to other seasons. The CH4 uptake rates were positively related to microbial biomass carbon (MBC) and labile C. Meanwhile, the CH4 uptake rate was exponentially correlated with inorganic nitrogen (N) concentration, suggesting the high inorganic N concentration in the cropland possibly inhibited the CH4 uptake rate. In afforested land, CH4 uptake rates positively correlated with soil temperature and negatively correlated with the C: N ratio. The αsoil was negatively related to soil temperature, whereas the δ 13 C values of CH4 remaining in the chambers were positively related to the δ 13 C values of soil organic carbon (SOC) and MBC. Our results suggest that the change in soil properties (i.e. high SOC and MBC, low C:N ratio and low inorganic N) following afforestation is a critical control on enhanced CH4 uptake capacity, while a lower αsoil further provides evidence for a high CH4 uptake rate in afforested lands. Highlights: Afforestation significantly enhanced the CH4 uptake capacity of soils. CH4 uptake rate in legume shrubland was higher than that in coniferous forest. Isotope fractionation factors were lower in afforested lands than cropland. Change in soil properties under afforestation is a critical control on CH4 uptake.